Localization of an aminoacridine antitumor agent in a type II topoisomerase-DNA complex. - Freudenreich, C H (1994)
Type II topoisomerases are the targets of several classes of chemotherapeutic agents that stabilize an intermediate of the catalytic cycle with the enzyme covalently linked to cleaved DNA. We have used 3-azido-AMSA [4'-(3-azido-9-acridinylamino)methanesulfon-m-anisidide], a photo-activatible analog of the inhibitor m-AMSA [4'-(9-acridinylamino)methanesulfon-m-anisidide], to localize the inhibitor binding site in a cleavage complex consisting of an oligonucleotide substrate and the bacteriophage T4 type II DNA topoisomerase. Upon photoactivation, the inhibitor covalently attached to the substrate only in the presence of topoisomerase. Sites of inhibitor attachment were detected by primer-extension analysis and by piperidine-induced cleavage of the covalently modified substrate. 3-Azido-AMSA reacted with bases immediately adjacent to the two phosphodiester bonds cleaved by the enzyme. Therefore, topoisomerase creates or stabilizes preferential binding sites for the inhibitor precisely at the two sites of DNA cleavage.